Magnetron sputtered TiO2 films on a stainless steel substrate : selective rutile phase formation and its tribological and anti-corrosion performance - Krishna, Dangeti Siva Rama (2012)
In this work, TiO2 films on 316L stainless steel have been formed by non-reactive magnetron sputtering of TiO2 target. The effect of a titanium underlayer on the crystalline phase of the TiO2 film has been investigated in terms of phase evolution, film morphology, corrosion resistance, adhesion strength, hardness and tribological characteristics. Results showed that the titanium underlayer has a significant effect on the phase of the TiO2 film. Without this underlayer, an anatase TiO2 film is produced, in consistence with many other investigations. However, it is found that with a titanium underlayer, a rutile TiO2 film can be directly formed on the substrate. The thickness of the interface layer affects the crystallinity of the rutile film. By controlling the underlayer thickness, the resultant rutile film crystal structure and morphology could be changed accordingly. At an optimized state, the rutile coating shows much improved adhesion, friction, wear and corrosion properties.